New prophylaxis strategies to reduce the risk of thromboembolism in cancer. Issue 10 (3rd October 2021) - Papadopoulos, Vasileios; Tsapakidis, Konstantinos; Markou, Alexandra; Kokkalis, Alexandros; Aidarinis, Chrissovalantis; Kotsakis, Athanasios
ABSTRACT: Introduction : Patients with cancer are at risk of thrombotic events, mainly deep vein thrombosis and/or pulmonary embolism. The thrombosis risk is generally 4–6 times higher than in a healthy population and depends on factors related to patient characteristics, tumor factors, and treatment-related factors. The decision-making for prophylactic anticoagulation is individualized according to the relative risks and benefits. The VTE risk has been quantified using different assessment scores. Areas covered : This article reviews current data and ongoing research on predictive factors involved in cancer-related thrombosis and highlights the currently suggested strategies for prophylaxis. Several trials that compared the two treatment options, direct factor Xa inhibitor or LMWH, with placebo and not each other are discussed. This article analyzed the safety and efficacy features that led several international organizations such as ASCO, NCCN, and others, to issue guidelines for the prophylaxis and treatment of patients at high risk of thrombosis by using LMWH, fondaparinux, and DOACs. Expert opinion : ASCO, NCCN, and other international organizations recommend thromboprophylaxis in high-risk patients. However, further investigation is needed to define better biomarkers for more accurate identification of cancer patients that will benefit from anticoagulant treatment.